Games as a teaching technique to enhance the grammatical competence among students of seventh year a of basic general education afternoon session, at unidad educativa fiscomisional Mercedes de Jesús Molina, in the city of Loja during 2020 – 2021 school year - Valarezo Lima, Angie Nicole (2021)
The objective of this research work was to enhance the grammatical competence through the application of games as a teaching technique among students of seventh year “A” of Basic General Education afternoon session, at Unidad Educativa Fiscomisional “Mercedes de Jesús Molina”, in the city of Loja during 2020-2021 school year. In this study, different methods were employed to describe, process, analyze and interpret the data, which were scientific, descriptive, statistical and analytical-synthetic. Tests and questionnaires were applied to twenty-eight students to obtain data about the grammatical competence, and observation sheets and field notes were administered to get information about learners’ attitudes. The results showed that students improved significantly in grammatical competence in the aspects of ordering words, recognizing tenses, and referring about verbs form. In conclusion, games allowed students to acquire and utilize grammar to convey an idea, motivate learners to participate, raise their grades and change their attitudes positively.